Effects of Accounting Conservatism on Financing through Banks and Financial Institutions in Firms listed in Tehran Stock Exchange - Abbas Aflatooni (Shahid Bahonar University of Kerman, 2016)
This research investigates the relationship between conditional/ unconditional accounting conservatism and the amount of financing through banks and financial institutions, in a sample of 138 firms listed in the Tehran Stock Exchange, from 2005 to 2013. This study also compares the impacts of conditional/ unconditional conservatism on the amount of loans received from banks and financial institutions. To measure the conditional and unconditional conservatisms, the criteria introduced by Khan and Watts (2009) and Beaver and Ryan (2000), respectively, were used.The results showed that increasing the degree of conditional/ unconditional conservatism leads to increasing in the volume of loans received from banks and financial institutions. In other words, banks and financial institutions are more eager to grant loans to the firms that accept higher degree of conservatism. Also, the results indicated that, compared with the unconditional conservatism, conditional conservatism has higher impact on the volume of loans received from banks and financial institutes.